2018
DOI: 10.1109/tnsre.2017.2740060
|View full text |Cite
|
Sign up to set email alerts
|

Generating Arm-Swing Trajectories in Real-Time Using a Data-Driven Model for Gait Rehabilitation With Self-Selected Speed

Abstract: Gait rehabilitation is often focused on the legs and overlooks the role of the upper limbs. However, a variety of studies have demonstrated the importance of proper arm swing both during healthy walking and during rehabilitation. In this paper, we describe a method for generating proper arm-swing trajectories in real time using only measurements of the angular velocity of a person's thighs, to be used during gait rehabilitation with self-selected walking speed. A data-driven linear time-invariant transfer func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Therefore, studying the swing angle fluctuation of the upper body is of great significance for determining the movement of the hand joint. Different from most research that used IMU to measure angular velocities of human body rods (Babak Hejrati et al, 2016;B. Hejrati, Merryweather, & Abbott, 2018;Shangjie et al, 2018), we explored the movement of upper limb joint angle during normal walking based on the marker point capture experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, studying the swing angle fluctuation of the upper body is of great significance for determining the movement of the hand joint. Different from most research that used IMU to measure angular velocities of human body rods (Babak Hejrati et al, 2016;B. Hejrati, Merryweather, & Abbott, 2018;Shangjie et al, 2018), we explored the movement of upper limb joint angle during normal walking based on the marker point capture experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al (Yuki, Tomoya, & Yuji, 2018) ever employed the equation for the elbow joint angle as the shoulder angle, it also verified the same cycle of shoulder joint and elbow joint. Hejrati et al (B. Hejrati et al, 2018) generated an arm-swing trajectory while a subject increased and then decreased walking velocity, as the subject slowed, the peak of arm angle decreased. This law can be verified relatively obvious in Fig.12 of Subject 1,3 and 4 when slow to stop.…”
Section: Discussionmentioning
confidence: 99%
“…The role of arm swing in human gait has been extensively investigated [1], and benefits such as torso rotational stability and reduced energy expenditure during walking have been reported for proper arm swing [2], [3]. Importantly, evidence suggests the existence of neural couplings between the upper and lower limbs and points to the crucial role of appropriate arm swing in interlimb coordination and improving the central pattern generator's function during gait training.…”
Section: Introductionmentioning
confidence: 99%
“…While the mentioned studies have shown promise for increasing arm swing amplitude, the effects of providing rhythmic tactile feedback to adjust the arm swing cycle time are unexplored. Previous research has shown that the arm swing frequency is directly and highly correlated with its amplitude and also walking speed and cadence [2], [34]. In this work, we (1) present a lightweight, wearable, and wireless feedback system capable of providing synchronized vibrotactile feedback to the arms.…”
Section: Introductionmentioning
confidence: 99%
“…In a study where the participants’ legs were suspended, in the majority of subjects, rhythmic motion of the arms in the antero-posterior direction elicited muscle activity and movement patterns in the legs similar to those created during walking [8]. Hejrati et al [9] created a data-driven linear time-invariant transfer function to predict the correct arm swing based on the realtime measurements of thighs’ angular velocity. The growing evidence for the role of arms in human locomotion has resulted in recommendations for their inclusion in rehabilitation or gait training of those with disrupted coordination abilities, such as stroke or Parkinson’s disease (PD) patients [10], [11].…”
Section: Introductionmentioning
confidence: 99%